The Book Review of “Designing Social Research: The Logic of Anticipation” - Hossein Salimi; Yazdan keikhosrou doulatyari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Designing Social Research: The Logic of Anticipation focuses specifically on the quantitative social research designs. The main objective of the book is the introduction of main elements in conducting research in social sciences. Moreover, it provides an appropriate review on issues that students, professors, and researchers of social sciences face in designing their research or thesis. Using technical terms of research methodology, unambiguous diction, and comprehensive elaboration all prove the efficiency of the author in writing such a scientific work. Most of the book has the sufficient literature review and its evolution. The author, Norman Blaikie, starts his introduction with preliminaries of research and its details. Introducing The Logic of Anticipation, pointing out the role of theory in social sciences research, and providing critical understanding of research principles are among main objectives of this book. Finally, the book presents four topics related to social research as examples for research in four paradigms (inductive, deductive, reproductive, and abductive).